A HIGH ALDOSTERONE TO RENIN RATIO MEDIATES MICROVASCULAR AND MACROVASCULAR DAMAGE IN NEWLY-DIAGNOSED, TREATMENT-NAÏVE ESSENTIAL HYPERTENSION. (April 2021) - Mahmud, Azra; Barhoumi, Tlili; Aklabi, Ali A.; Feely(Late), John; Silke, Bernard
Abstract : Objective: The role of aldosterone in hypertension was generally considered in the context of primary hyperaldosteronism, an uncommon condition (less than 2% in the hypertensive population). However, based on an increased ambulant aldosterone-to-renin ratio (ARR), a marker of inappropriate aldosterone activity, the prevalence of primary hyperaldosteronism in the hypertensive population may be as high as 10% to 15%. There is increasing evidence to suggest a BP-independent effect of aldosterone on left ventricular structure, increased collagen deposition with fibrosis, diastolic dysfunction and arterial stiffness. We hypothesized that aldosterone and renin will be associated with microvascular and macrovascular alterations in never treated essential hypertension. Design and method: We prospectively studied newly diagnosed, untreated essential hypertensive and normotensive subjects (n = 1482, 47% females, mean age 51 ± 0.77, SEM). Pulse wave velocity (PWV), augmentation index (AIx), aortic systolic BP and pulse pressure amplification were measured with applanation tonometry(SphygmoCor). Albumin-creatinine ratio, urine sodium and potassium concentrations were determined from spot urine samples. Laboratory tests included serum creatinine and clearance, plasma renin activity, serum aldosterone, and high-sensitivity C-reactive protein(hs-CRP). Aldosterone to renin ratio(ARR) was divided into tertiles. Results were analysed using JMP Pro(Version 13, SAS for Windows). The patients gave informed consent and the study had Institutional ethics committee permission. Results: The top ARR tertile was associated with the highest levels of brachial BP, aortic systolic BP, AIx, pulse pressure amplification and PWV(P < 0.001 for all). Stepwise regression analysis showed that the positive association between PWV and increasing ARR tertiles remained significant after adjustment for BP, age and other potential confounders(R2 = 0.39, p < 0.05). The top ARR tertile was also associated with high potassium and low sodium urinary excretion, high ACR, low creatinine clearance and high hs-CRP (All p < 0.01). Conclusions: In untreated hypertensive subjects with mild to moderate hypertension, there are significant interactions between ARR and indices of microvascular and macrovascular damage. Our findings indicate that aldosterone and renin adversely modulate microvascular and macrovascular function very early in the evolution of hypertension. While aldosterone antagonism is recommended currently for treatment-resistant hypertension, our findings suggest that it should be initiated early in hypertension.